228k views
3 votes
Please Help Me Thanks​

Please Help Me Thanks​-example-1

2 Answers

0 votes

Explanation:

Hey there!

Given;


√(4x - 2) + 3 = 5

Shift "3" on right side.


√(4x - 2) = 5 - 3


√(4x - 2) = 2

Squaring on both sides.


{( √(4x - 2) )}^(2) = {2}^(2)

Simplify it.


4x - 2 = 4


4x = 4 + 2


x = (6)/(4)


x = (3)/(2)

Therefore, X = 3/2.

Hope it helps...

User TRuEsAtM
by
5.5k points
3 votes

We are given the equation:

√(4x - 2) + 3 = 5

Subtracting by 3 on both sides

√(4x - 2) = 2

Squaring both sides

4x - 2 = 4

Adding 2 on both sides

4x = 6

x = 3/2

User Jedidias
by
4.9k points